Transformasi Blok Saraf Sensoris untuk Prosedur Bebas Nyeri dengan Levobupivacaine - Raymond R. Tjandrawinata (MEDICINUS, 2026)
Procedural pain is a biological consequence arises from the activation of peripheral nociceptors, the transmission of impulse through sensory nerve fibers, spinal processing, and cortical integration that transforms tissue injury into a conscious pain experience. Modern clinical practice increasingly recognizes that pain-free procedures should not belimited to postprocedural analgesia, but should involve precise interventions targeting pain transmission pathways before nociceptive impulses evolve into a systemic responses and psychological burden. Sensory nerve block represents an important clinical approach because it acts directly on peripheral transmission structures, aiming to inhibit pain impulse conduction without inducing extensive depression of consciousness. Levobupivacaine, a long-acting amino-amide localanesthetic and the S-enantiomer of bupivacaine, provides a pharmacologically relevant option for this transformation. By inhibiting voltage-gated sodium channels on neuronal membranes and stabilizing their inactive state, levobupivacainereduces neuronal excitability and reversibly interrupts the sensory transmission pathway. This medical perspective frames sensory nerve block not merely as a regional anesthetic technique, but as part of a broader shift toward procedures thatare more targeted, mechanism-based, anatomically precise, patient-centered care, more humane, and align with the physiology of pain. The challenges associated with this approach include appropriate patient selection, comprehensive anatomical understanding, technical precision, toxicity awareness, and the integration of sensory nerve blocks into rational perioperative pain management.